A solution-phase synthesis method to prepare Pd-doped carbon aerogels for hydrogen storage. Issue 27 (23rd February 2015) - Zhong, Minglong; Fu, Zhibing; Yuan, Lei; Zhao, Haibo; Zhu, Jiayi; He, Yongwei; Wang, Chaoyang; Tang, Yongjian
Abstract : A solution-phase synthesis method was studied to prepare Pd-doped carbon aerogels (Pd/CAs) with different contents. Abstract : A solution-phase synthesis method was studied to prepare Pd-doped carbon aerogels (Pd/CAs) with different contents. The physical properties of the pristine CAs and Pd/CAs were systematically characterized by X-ray diffraction, transmission electron microscopy, scanning electron microscopy, and N2 adsorption measurements. We concluded that increasing Pd content produced an increase of the metal particle size and decrease of the surface area of the CAs. The effects of different amounts of palladium loading on the hydrogen uptake capacities of CAs have been investigated. The results show that Pd doping has a negative effect on hydrogen uptake capacity at 77 K. At 298 K, hydrogen uptake capacity depends on Pd content and particle size in the low pressure region (<10 bar). The hydrogen uptake capacity of the 4.8 wt% Pd/CA is about 0.11 wt% at 10 bar and 298 K. For higher pressure (>10 bar), the pore volume controls hydrogen uptake capacity.